2015
DOI: 10.4049/jimmunol.1402071
|View full text |Cite
|
Sign up to set email alerts
|

MF59 Mediates Its B Cell Adjuvanticity by Promoting T Follicular Helper Cells and Thus Germinal Center Responses in Adult and Early Life

Abstract: The early life influenza disease burden calls for more effective vaccines to protect this vulnerable population. Influenza vaccines including the MF59 oil-in-water adjuvant induce higher, broader, and more persistent Ab responses in adults and particularly in young, through yet undefined mechanisms. In this study, we show that MF59 enhances adult murine IgG responses to influenza hemagglutinin (HA) by promoting a potent T follicular helper cells (TFH) response, which directly controls the magnitude of the germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 56 publications
4
60
3
Order By: Relevance
“…We recently demonstrated that MF59 is highly effective in juvenile (3-week-old) animals, and MF59 has also been shown to improve immunogenicity in children over 6 months old (30), but it had limited efficacy in 1-week-old mice and has not been tested in younger infants. In the current study, we demonstrated that NanoSiO2 was effective in early life, leading to a significant reduction in disease following infection compared to the results seen with antigen alone.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that MF59 is highly effective in juvenile (3-week-old) animals, and MF59 has also been shown to improve immunogenicity in children over 6 months old (30), but it had limited efficacy in 1-week-old mice and has not been tested in younger infants. In the current study, we demonstrated that NanoSiO2 was effective in early life, leading to a significant reduction in disease following infection compared to the results seen with antigen alone.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest and most abundantly recruited cell type is neutrophils, followed by monocytes, eosinophils and later dendritic cells (DCs) and macrophages. After the recruitment of immune cells into the injection site, MF59 can accelerate and enhance monocyte differentiation into DCs, augment antigen uptake, and facilitate migration of DCs into tissue-draining lymph nodes to prime adaptive immune responses [37-39]. The combination of MF59 adjuvant dramatically improved immunogenicity of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Squalene emulsified with surfactants serves as an adjuvant (MF59 and AS03) that drives robust antibody responses, polyfunctional TH1 cells and TFH cells, and enhanced immunity to heterotypic strains of influenza [7782]. Uniquely, antibody isotype switching is induced by MF59 in the absence of CD4 + T cells, however apparently the plasma cells making this antibody don’t live for a long time in the absence of T cell help [83].…”
Section: Emulsion Based Adjuvantsmentioning
confidence: 99%